EFFECTS OF REMITTANCES ON POVERTY REDUCTION: THE CASE OF INDONESIA - Faiza Husnayeni Nahar; Mohd Nahar Mohd Arshad (Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
Remittances have been reported as a tool for fighting poverty in some selected countries, such as Indonesia. An increase of income through remittances tends to improve the economic status of the migrant’s household. Once they get a high salary, they will remit money (a remittance) to their household in Indonesia via formal institutions, such as banks. The migrant’s household can fulfil their basic needs and can use the remittance for educational investment and productive activities. The education investment aims to educate the children or grandchildren of migrants, which will be beneficial for the future generations of the family, allowing them the chance of a more prosperous life. The poverty rate would be reduced gradually, and economic welfare can be achieved. The main objectives of this paper are first to estimate the effects of remittances on poverty in Indonesia from 1983 to 2015 and second, to propose several strategic policies related to remittances and poverty reduction. Other variables considered include inflation, exchange rates, income, income inequality and the labor force participation rate. An Ordinary Least Square (OLS) method was used to explore the econometric and estimated results. The study found that an increase in remittances led to a reduction in poverty by 2.56%. Inflation and the exchange rate have positive and negative effects on poverty, respectively. The small effect of remittances on poverty’s reduction could possibly be explained by the low educational background of the migrants, low wage jobs, expensive remittance costs, and migrants not knowing how to remit money through formal financial institutions. Hence, to reduce the poverty level, the government needs to first facilitate skills training for the workers so that they could get a better job and earn more, second, lower the transaction costs of remittances, and lastly, provide agents at Indonesian banks overseas to provide better facilities to Indonesian workers to remit money back to their home country.